2001
DOI: 10.1084/jem.193.11.1269
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Adaptor Protein Trim Regulates T Cell Receptor (Tcr) Expression and Tcr-Mediated Signaling via an Association with the Tcr ζ Chain

Abstract: T cell receptor (TCR)-interacting molecule (TRIM) is a recently identified transmembrane adaptor protein, which is exclusively expressed in T cells. Here we demonstrate that in mature T cells, TRIM preferentially interacts with the TCR via the TCR-ζ chains and to a lesser extent via the CD3-ε/γ heterodimer. Transient or stable overexpression of TRIM in Jurkat T cells results in enhancement of TCR expression on the cell surface and elevated induction of Ca2+ mobilization after T cell activation. TRIM-mediated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 37 publications
4
76
1
Order By: Relevance
“…Ahmed and coworkers (2) recently showed that the IL-7 receptor is selectively expressed in MEM T cells. The T cell receptor-interacting molecule is a recently identified transmembrane adaptor protein that is exclusively expressed in mature T cells (15). EFFE up, MEM intermediary, NAI down.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed and coworkers (2) recently showed that the IL-7 receptor is selectively expressed in MEM T cells. The T cell receptor-interacting molecule is a recently identified transmembrane adaptor protein that is exclusively expressed in mature T cells (15). EFFE up, MEM intermediary, NAI down.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not fully understood how TCR surface expression levels are regulated, it seems to involve protein kinases (2,9,10,19), phosphorylation status of the TCR chains (9,19), and adaptor proteins such as TCR-interacting molecule (35,36) and src-like adaptor protein (30). The present study was performed to broaden our knowledge of the mechanisms regulating constitutive TCR cycling and ligand-induced TCR internalization.…”
Section: Discussionmentioning
confidence: 99%
“…3), making the TCR␣␤: strategy more universal with respect to TCR-V regions. In addition, the enhanced surface expression and function of TCR␣␤: may be linked to TCR-interacting molecule, an adaptor molecule that normally associates with CD3 and contributes to TCR expression and signaling (48). Also, the absence of glycosylation sites that are normally present in TCR-C␣ and ␤ (a total of four sites in human TCR␣␤) may result in enhanced expression and avidity of TCR␣␤: (55).…”
Section: Discussionmentioning
confidence: 99%